Importance of Archaeological Evidence in Quranic Studies: In the Light of Urdu Exegeses - Hafiz Muhammad Saeed; Usama Siddiqui (jihat-ul-islam, 2020)
In Urdu exegetic literature, evidences have been taken, when needed, from the signs of the cursed nations. If the mufassirin get some authentic archaeological information about these remaining signs, they include the same in their exegesis. They also seem to be taking evidences from the latest research in the field of archaeology. As in today’s world archaeology has assumed the role of a proper science, its research and archaeological support cannot be ignored or undervalued. And in such debates, the role of archaeology emerges as the servant of the Quran. In the contemporary world archaeology, by using the latest technology, has helped locate and analyse the details about the cursed land of the Prophet Lot (AS) and the overturned towns in the seabed. In this way, the clear statements and orders of the Quran have been authenticated word for word. This authentication is a source of evidence for many mufassirin especially the Urdu mafassirin. In this way, the scientific help provided by archaeology brings the truths upheld by the Quran to light. This evidence has facilitated a best exegesis of the archaeological places mentioned in the Quran. By employing the insights and evidences provided by the modern archaeology, the mufassirin have uncovered for the mankind different aspects of the Quran loaded with visual proofs carrying reproof and warning.